2014
DOI: 10.1186/s12863-014-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Wild barley introgression lines revealed novel QTL alleles for root and related shoot traits in the cultivated barley (Hordeum vulgareL.)

Abstract: BackgroundRoot is the prime organ that sucks water and nutrients from deep layer of soil. Wild barley diversity exhibits remarkable variation in root system architecture that seems crucial in its adaptation to abiotic stresses like drought. In the present study, we performed quantitative trait locus (QTL) mapping of root and related shoot traits under control and drought conditions using a population of wild barley introgression lines (ILs). This population (S42IL) comprising of genome-wide introgressions of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 44 publications
(47 reference statements)
13
82
0
Order By: Relevance
“…However, excessive tillering resulted in the initiation of more nodal roots suggested the dependence of shoot and root development. Similar results were reported earlier by Arifuzzaman et al (2014) and Naz et al (2014) where a putative QTL region was found for Rdw and related shoot traits on chromosome 1H in barley. To find the putative candidate gene underlying this variation, we identified 10 putative genes of different categories in the targeted QTL interval using barley genome sequence (Mayer et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, excessive tillering resulted in the initiation of more nodal roots suggested the dependence of shoot and root development. Similar results were reported earlier by Arifuzzaman et al (2014) and Naz et al (2014) where a putative QTL region was found for Rdw and related shoot traits on chromosome 1H in barley. To find the putative candidate gene underlying this variation, we identified 10 putative genes of different categories in the targeted QTL interval using barley genome sequence (Mayer et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Naz et al. () and Arifuzzaman et al. () reported an increasing Hsp effect on root dry weight in S42IL‐133, where we found a reducing effect in the same line under P stress.…”
Section: Discussionsupporting
confidence: 75%
“…The root dry weight increasing Hsp effects present in S42IL‐102 and ‐176 were also reported under drought stress by Naz, Ehl, Pillen, and Leon () and Naz et al. (). In addition, Naz et al.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By contrast, plants using a drought avoidance strategy maintain sufficient cellular hydration when water is scarce [21–23]. Common drought avoidance mechanisms in barley include minimizing water loss via stomatal control [24], production of extensive root system to extract soil moisture [25, 26], and altering metabolism to accumulate compatible solutes (osmolytes) for osmotic adjustment [27, 28]. Drought tolerant varieties maintain physiological functions at low tissue water potentials [21, 22].…”
Section: Introductionmentioning
confidence: 99%